Identification and Characterization of Green Microalgae, Scenedesmus sp. MCC26 and Acutodesmus obliquus MCC33 Isolated From Industrial Polluted Site Using Morphological and Molecular Markers - Sarwa, Prakash; Verma, Sanjay Kumar (International Journal of Applied Sciences and Biotechnology, 2017)
Two unicellular green microalgae, were isolated from Amani Shah Nallah (Jaipur, India) that receives discharge of dyeing industries. Preliminary morphological characterization using light microscopy showed ovoid, fusiform shape of cells with single to two celled coenobia in a culture suspension. Transmission electron microscopy (TEM) analyses depict abundant chloroplast located at the periphery of the cell, a pyrenoid as well as nucleus is visible in the centre. A well developed cell wall with many layers is also evident in TEM. Phylogenetic position and genetic variabilty among the isolated microalgal strains were investigated by 18S rDNA sequence analysis. The results suggest that the isolated microalgae belongs to family chlorophyceae and corresponds to genus Scenedesmus and genus Acutodesmus. Growth profile of both microalgal strains showed a typical sigmoid curve with specific growth rate of µmax, 0.839 day-1 and 0.654 day-1 for Scenedesmus sp. and Acutodesmus obliquus, respectively. The strains were allotted with MCC numbers by IARI, New Delhi as MCC26 for Scenedesmus sp. and MCC33 for Acutodesmus obliquus. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 415-422